The effect of permissibility and grammatical conditions on diversifying meanings - Al Rahawi, Mohammed Khaled (Arab Journal for Sciences and Research Publishing, 2018)
Arabs were men of eloquence and manifestation in speech. They were supported by their language " Arabic" with what it possessed of a wide range of vocabulary and accuracy in showing the meaning and flexibility of structures. The task of the grammarians, in a large deal of it, was only describing the flexibility of the structures rather than inventing ways of expressions only to enlarge the number, of the ways. However, who reads what the grammarians have allowed and stipulated in some rules, without scrutinizing it he may think, as some researchers claim that it was only for enlarging the number or shortening without following what had been admitted in the structure or what had been provided in the rule of "changing" in the meaning. This research tries to show that the Grammatical Permissibility functions for variating the meanings by means of showing the tiny differences between the meanings that some of which other aspects have been permitted. And in demonstrating how the change of the vowel points show the meanings approving that the matter is not as it has been claimed. So for that aim I’ve chosen quests that I find in them two or three aspects such as the Amputated Adjective which is devoted for praising or dispraising and "Belhe" and some others. I’ve also chosen the quest of "the subject Representation" on which the grammarians, conditions "term" are many. I’ve shown that these conditions have been established according to the meaning and for it. Then finally I concluded with the consequences yielded by the research.